Internet marketing e-commerce and cyber laws - Narayan, Asit; Thakur, L K (Delhi Authors Press, 2000)
This book is a compendium to the many facets of internet marketing,e-commerce and cyber laws and make use of today's technology to solve business communication and computer intensive transactions.This book will serve as a complete guide to students, polic
Keywords: Electronic commerce; Internet marketing; Electronic commerce-Law and legislation